2022
DOI: 10.1128/spectrum.00395-22
|View full text |Cite
|
Sign up to set email alerts
|

Differential Infectivity of Original and Delta Variants of SARS-CoV-2 in Children Compared to Adults

Abstract: These important findings show that children may play a larger role in viral transmission of Delta than for previously circulating SARS-CoV-2 variants. Additionally, they may suggest a mechanism for why Delta has evolved to be the predominant circulating variant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Individuals under 18 years old reported an average number of 11.27 contacts per day (Table 1 and Figure S6). The sensitivity analysis underlined a notable decrease in the elasticity of the Characterized by increased transmissibility and potential to evade vaccine-induced immunity 41,43,44 , the Delta VOC represented over 50% of the sequenced new cases at the beginning of July 2021 56,57 . Concurrently, the progress of vaccination across adult age groups, notably extending to young adults during summer 2021 52,55 , further altered the susceptibility profile of the population.…”
Section: /19mentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals under 18 years old reported an average number of 11.27 contacts per day (Table 1 and Figure S6). The sensitivity analysis underlined a notable decrease in the elasticity of the Characterized by increased transmissibility and potential to evade vaccine-induced immunity 41,43,44 , the Delta VOC represented over 50% of the sequenced new cases at the beginning of July 2021 56,57 . Concurrently, the progress of vaccination across adult age groups, notably extending to young adults during summer 2021 52,55 , further altered the susceptibility profile of the population.…”
Section: /19mentioning
confidence: 99%
“…Subsequently, research has pointed to the crucial role of the pediatric population in virus transmission, particularly in school and household settings 11,[31][32][33][34] . The emergence of more transmissible virus VOCs such as Alpha [35][36][37][38][39][40] , Delta [41][42][43][44][45] , and Omicron 35,46,47 further complicated this scenario, leading globally to an increase in virus prevalence and transmission risk within the pediatric population [34][35][36]48 . These findings became progressively clearer considering the gradual resumption of school activities and the consequent increased exposure of younger populations.…”
Section: Introductionmentioning
confidence: 99%
“…A second study reported both RNA viral load and level of infectious virus using a semi-quantitative method (TCID 50 ) in paediatric clinical samples, which revealed that neither age nor disease severity impacted on viral load [ 7 ]. In contrast, however, others have found that children have decreased levels of viral RNA, lower infectious virus titres as measured by TCID 50 and are less likely to have virus successfully isolate in cell culture as compared to adults [ 8 ], although paediatric delta variant infections increase the culture-positive viral titres to comparable levels to adults [ 9 ]. Other work indicates that ancestral SARS-CoV-2 replicates less efficiently in both children and paediatric versus adult nasal epithelial cells, a defect that omicron was able to abolish [ 10 ].…”
Section: Introductionmentioning
confidence: 99%